2015
DOI: 10.1088/0067-0049/219/2/28
|View full text |Cite
|
Sign up to set email alerts
|

ISOTOPIC RATIOS OF 18 O/ 17 O IN THE GALACTIC CENTRAL REGION

Abstract: O abundance ratios toward the GC region relative to molecular clouds in the Galactic disk. Furthermore, even inside the GC region, ratios appear not to be uniform. The low GC values are consistent with an inside-out formation scenario for our Galaxy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…It is 4.35±0.45 and >5.27 for sources at 3 kpc<D GC <11 kpc and D GC >11 kpc, respectively which is consistent with their results. Combining with our mapping results that provide a ratio value of 3.01±0.14 in the Galactic cen-ter region (Zhang et al 2015), a linear least-squares fit gives 18 O/ 17 O=(0.18±0.04)D GC +(2.91±0.27), with a Spearman's rank correlation coefficient R = 0.85. However, we have to note that our sources with galactocentric distance larger than 11 kpc are still not enough, and the J = 1 − 0 transitions alone (C 18 O and C 17 O) are not sufficient when trying to account for radiative transfer effects.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is 4.35±0.45 and >5.27 for sources at 3 kpc<D GC <11 kpc and D GC >11 kpc, respectively which is consistent with their results. Combining with our mapping results that provide a ratio value of 3.01±0.14 in the Galactic cen-ter region (Zhang et al 2015), a linear least-squares fit gives 18 O/ 17 O=(0.18±0.04)D GC +(2.91±0.27), with a Spearman's rank correlation coefficient R = 0.85. However, we have to note that our sources with galactocentric distance larger than 11 kpc are still not enough, and the J = 1 − 0 transitions alone (C 18 O and C 17 O) are not sufficient when trying to account for radiative transfer effects.…”
Section: Discussionsupporting
confidence: 65%
“…We are undertaking a systematic observational study on the ratio of 18 O to 17 O. This includes detailed mapping towards more molecular clouds in the Galactic center (Zhang et al 2015) and single point observations toward disk molecular clouds with different galactocentric distances, especially more sources with large galactocentric distances, to check the existence of the ratio 18 O/ 17 O gradient along the Galactic disk (this work).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to also cover the inner region of the Milky Way to find out whether the trend proposed by Chin et al (1996) is also valid for the inner Galaxy as has been reported for the 12 C/ 13 C (see e.g. Yan et al 2019), 14 N/ 15 N (Adande & Ziurys 2012) and 18 O/ 17 O (Wouterloot et al 2008;Zhang et al 2015) isotopic ratios.…”
Section: A222 Page 1 Of 15mentioning
confidence: 91%
“…As is shown in Figure 2, the peak intensities of OH are -0.03 K and -0.15 K for Sgr B2(N) and Sgr B2(M), respectively. Since 16 O/ 17 O is observed to be up to 1000 in Sgr B2 (Polehampton et al 2005;Zhang et al 2015), 17 OH should appear as absorption line with very low peak intensity, which could be ignored safely.…”
Section: Line Identificationsmentioning
confidence: 99%